The Flag of Distress: A Story of the South Sea - Reid, Mayne, 1818-1883 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Flag of Distress: A Story of the South Sea" by Captain Mayne Reid is a novel written in the mid-19th century. The story unfolds around a mysterious barque displaying an inverted Chilian flag, signaling distress but sailing away at full speed, prompting a British frigate to pursue it. The tale begins with the intriguing chase across the Pacific, revealing strange elements such as the unusual clothing of the barque's crew and the possibility of supernatural events, setting the stage for an adventurously captivating narrative. The opening of the novel introduces us to a British naval frigate chasing a Chilian barque that is signaling for help with its flag upside down, despite being under full sail. As the captain and crew pursue this seemingly distressed vessel, they begin to ponder the enigma behind its behavior. Initially dismissing the barque as a phantom, the crew's curiosity intensifies once they spot strange figures aboard, later revealed to be orangutans. This fascinating premise sets the tone for an adventure filled with mystery and the promise of unraveling a deeper saga involving the fate of the missing crew and the adrift barque itself. (This is an automatically generated summary.)
Release date is 2008-04-25
Produced by Nick Hodson of London, England
Keywords: Christian life -- Juvenile fiction; Seafaring life -- Juvenile fiction; Rescues -- Juvenile fiction; Sailors -- Juvenile fiction; Mutiny -- Juvenile fiction; Shipwrecks -- Juvenile fiction